Meaning of Science Concepts (Study Analysis of the Meaning of Science According to Syed Naquib Al-Attas) - Nirhamna Hanif Fadillah; Mohammad Hanief Sirajulhuda; Amir Reza Kusuma (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2025)
The concept of science which was initiated by Syed Muhammad Naquib Al-Attas above, the most emphasized is one's worldview in looking at science. How does Al-Attas explain the nature of knowledge from where, then how do humans obtain it, how to be fair in putting knowledge, so that a good Muslim is formed, in relation to the macrocosm, microcosm, and the being behind it all, namely the form of the universe. Lord. Everyone has their own worldview in viewing reality. Therefore, the composition of the concept of Al-Attas science is built on an Islamic worldview, it is hoped that a Muslim will use his Islamic worldview in viewing reality and truth. both propositions and ontologies. The method of acquiring knowledge is also different from the Western concept, where al-Attas explains that there are several intermediaries, namely healthy senses, khabar sadiq, common sense, and intuition.